Intrauterine IPEX - Carneiro-Sampaio, Magda; Moreira-Filho, Carlos Alberto; Bando, Silvia Yumi; Demengeot, Jocelyne; Coutinho, Antonio (Frontiers in Pediatrics, 2020)
IPEX is one of the few Inborn Errors of Immunity that may manifest in the fetal period, and its intrauterine forms certainly represent the earliest human autoimmune diseases. Here, we review clinical, histopathologic, and genetic findings from 21 individuals in 11 unrelated families, with nine different mutations, described as cases of intrauterine IPEX. Recurrent male fetal death (multigenerational in five families) due to hydrops in the midsemester of pregnancy was the commonest presentation (13/21). Noteworthy, in the affected families, there were only fetal- or perinatal-onset cases, with no affected individuals presenting milder forms with later-life manifestation. Most alive births were preterm (5/6). Skin desquamation and intrauterine growth restriction were observed in part of the cases. Fetal ultrasonography showed hyperechoic bowel or dilated bowel loops in the five cases with available imaging data. Histopathology showed multi-visceral infiltrates with T lymphocytes and other cells, including eosinophils, the pancreas being affected in most of the cases (11/21) and as early as at 18 weeks of gestational age. Regarding the nine FOXP3 mutations found in these cases, six determine protein truncation and three predictably impair protein function. Having found distinct presentations for the same FOXP3 mutation in different families, we resorted to the mouse system and showed that the scurfy mutation also shows divergent severity of phenotype and age of death in C57BL/6 and BALB/c backgrounds. We also reviewed age-of-onset data from other monogenic Tregopathies leading to IPEX-like phenotypes. In monogenic IPEX-like syndromes, the intrauterine onset was only observed in two kindreds with IL2RB mutations, with two stillbirths and two premature neonates who did not survive. In conclusion, intrauterine IPEX cases seem to constitute a particular IPEX subgroup, certainly with the most severe clinical presentation, although no strict mutation-phenotype correlations could be drawn for these cases.